2003
DOI: 10.1007/s103100300010
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between salt tolerance and proline accumulation in Australian acacia species

Abstract: The effects of salinity on the seedlings of five acacia species, Acacia ampliceps, A. salicina, A. ligulata, A. holosericea, and A. mangium were studied with respect to mortality, growth, and proline accumulation. There was marked variation among the species in their response to salinity. A. ampliceps showed the highest level of salt tolerance among the five acacia species. In contrast, A. holosericea and A. mangium were classified as the least tolerant. The concentration which caused 100% mortality in 2-wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 22 publications
3
9
0
Order By: Relevance
“…Total protein (TP) and insoluble protein (InsP) fractions were significantly decreaed in NaClstressed leaves (Table 1), this was accompanied with an increase of SP, SP/TP and proline contents (Table 3). These results are consistent with the findings of other authors (Sairam et al, 2002;Yokota, 2003;Sumithra et al, 2006 andHossain et al, 2012). In contrast, Hossain et al (2012) have reported that SP content in tomato plants was markedly decreased under salt stress.…”
Section: Discussionsupporting
confidence: 94%
“…Total protein (TP) and insoluble protein (InsP) fractions were significantly decreaed in NaClstressed leaves (Table 1), this was accompanied with an increase of SP, SP/TP and proline contents (Table 3). These results are consistent with the findings of other authors (Sairam et al, 2002;Yokota, 2003;Sumithra et al, 2006 andHossain et al, 2012). In contrast, Hossain et al (2012) have reported that SP content in tomato plants was markedly decreased under salt stress.…”
Section: Discussionsupporting
confidence: 94%
“…(Nawaz et al, 2010), and as a result inhibit seed germination and seedlings plant growth (Jamil et al, 2006;Basalah, 2010). Though it has been noted that trees can still tolerate salinity to a certain extent when compared with agricultural field crops (Niazi et al, 1985;Ali et al, 1987), our result further confirms that seed germination, growth and survival of trees are still sensitive to salinity at their seedling stage (Ramoliya and Pandey, 2002;Yokota, 2003;Parsons, 2004).…”
Section: Discussionsupporting
confidence: 85%
“…The plants of the acacia family appear to have the potential to grow in salty soils [39], with considerable differences in sensitivity to salt stress among species [40] [41]. The tolerance of a plant to salt stress, linked to its genetic potential, could [53] noted that the growth of the shoot parts of tomato was increased by inoculation with AMF from non-saline areas and was inhibited by inoculation with AMF from saline areas.…”
Section: Discussionmentioning
confidence: 99%